DETERMINAN KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Hoki Samuel; Mila Susanti (Jurnal Saintifik, 2023)
The Indonesian government had an abundance of resources but still sets taxes as a source of state revenue. This strategy were used so that the people have high competitiveness. One of them was through motor vehicle tax. The tax target was achieved if there was taxpayer compliance in paying taxes. Therefore, this research looked for things that encourage taxpayers to comply with paying motor vehicle taxes. Primary data was collected from 87 respondents who became the sample data of this study to motor vehicle owners in one of the villages in West Bandung Regency. The research analysis utilized descriptive methods and correlation techniques along with associative hypothesis testing. The results of data processing found that knowledge about taxation, quality of tax services, tax sanctions, and technology in tax services had a significant effect on taxpayer compliance partially and significantly. The summary that could be drawn from this research was that knowledge, service quality, tax sanctions and the use of technology have an impact on the compliance of taxpayers in the environment. However, it could be seen from the results that greater efforts were still needed to improve the compliance of motor vehicle taxpayers.